COMPARISON OF OVIPOSITION SITE PREFERENCES IN BLACK SOLDIER FLY (Hermetia illucens) AGAINST VARIOUS ATTRACTANTS - Anggia, Rachel
Black soldier flies (Hermetia illucens) are insects that used as one of the biological agents to control organic waste by turning it into economically valuable biomass. In terms of maximizing the ability of these insect, artificial maintenance and life cycle engineering of black soldier flies is needed to be carried out in order to obtain an optimal process of reducing organic waste and increasing biomass harvest. One limiting factor in the use of these insect on a large scale is on egg production. In egg production egg traps are used in combination with attractant media. The use of egg traps and attractant media aims to facilitate egg harvesting to be more effective because eggs will be concentrated in one location. This cause attractant media to be an important component that determines the preference of the female flies for laying eggs in a trap. In this research, the performance of various attractant media was tested in an effort to find the most optimal material in attracting black soldier flies to lay eggs on egg traps. The attractant media used were rotten cabbage, rotten papaya, tofu pulp and fish meal. The performance of attractant media is then evaluated based on the egg weight obtained in the egg trap. This study reports that most attractants can attract black soldier flies. Based on the results of statistical tests with Kruskal-Wallis, it is known that there are significant differences in egg weight obtained from each attractant used in which the attractant in the form of fish meal is the most effective attractant with an average egg weight per trap is 2.17 gr. On the other hand attractants made from tofu pulp are attractants that are at least desirable where the average weight of eggs per trap is 0.06 gr.